(De)hydratases — recent developments and future perspectives. (April 2018) - Demming, Rebecca M; Fischer, Max-Philipp; Schmid, Jens; Hauer, Bernhard
Graphical abstract: Highlights: Cofactor-independent (de)hydratases as promising enzymes for organic synthesis. Fatty acid hydratases, linalool dehydratase isomerase and carotenoid hydratases are discussed. Recent developments comprise crystal structures and detailed mechanistic understanding. Extension of substrate scope was achieved and mutagenesis studies were performed. Abstract : Hydratases have gained attention as alternative to chemical catalysts for their ability to add and eliminate water with high regio-selectivity, stereo-selectivity and enantio-selectivity. Recently, especially cofactor-independent hydratases came into research focus as they are of particular interest for industrial application. The investigation of the substrate scope as well as mutagenesis studies combined with high-resolution crystal structures and bioinformatic methods shed light on this promising enzyme class. This review presents latest findings in the field of fatty acid hydratases, linalool dehydratase isomerase and carotenoid hydratases focusing on mechanistic und structural aspects as well as the expansion of the substrate scope and new applications in organic synthesis.